Multilevel Design in the Implementation of Blended Learning in Nonformal Education Unit - Shantini, Yanti; Hidayat, Dayat; Oktiwanti, Lesi; Mitsuru, Takahashi (Journal of Nonformal Education, 2021)
CLC as one of the non-formal educational institutions affected by the COVID 19 outbreak must organize online teaching and learning activities under government instructions as an effort to prevent transmission of the COVID 19 pandemic.Â  Lack of experience in conducting online learning makes institutions confused about running the learning process due to educators and managers' limited ability to implement online education. It is necessary to study more deeply what learning strategies CLCs should carry out during the pandemic period. The approach used in this study was a mixed-method with 10 CLC respondents spread across West Java. From the findings in the field, learning at CLC during the pandemic was still ongoing. Tutor only used message applications for delivering learning material and evaluation process. They do not even implement it in the online learning management system. For this reason, CLC can pilot a multilevel blended learning system model. The implementation of the model system starts from institutional management, program management, to learning management by tutors.